PENERAPAN METODE DEMONSTRASI DALAM KEGIATAN MENGUKUR UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK - Putri Clawson; Ratna Yuwita (P3M STKIP 'Aisyiyah Riau, 2018)
Based on observations made by researchers at Asri Kindergarten, Rumbai Coastal District of Pekanbaru in Group B, the results show that children's cognitive abilities in measuring are still low. Therefore it needs to be increased again. The purpose of this study is to determine whether the application of demonstration methods in measuring activities can improve cognitive development of children aged 5-6 years at Asri Kindergarten, Pekanbaru. This type of research is PTK (Classroom Action Research). This research was conducted in two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. Each cycle has three meetings. While the data collection instruments used were interviews or questions and answers with children, teacher and child observation sheets and documentation. The results obtained after conducting classroom action research in B3 Asri kindergarten children are the application of demonstration methods in measuring activities to improve cognitive development of children aged 5-6 years at TK Asri Pekanbaru. The results of the calculation of what percentage increase in cognitive development abilities of children of the Asri B3 group in the initial condition of cognitive development of the seven criteria observed was at 44%, in the first cycle increased to 63%, an increase of 19%, in the second cycle increased to 88% with 25% increase.